Perubahan Perilaku Menyampah Siswa Melalui “Reinforcement” - Ningrum, Vanda; Vibriyanti, Deshinta; Hidayati, Inayah; Putri, Intan Adhi Perdana; Katherina, Luh Kitty; Seftiani, Sari (Jurnal Sosial Humaniora, 2025)
Littering behavior studies are essential amid high waste conditions in Indonesia. This study aims to analyze student littering behavior changes through a reinforcement program in Junior High School in Depok, West Java. Using an explorative-qualitative approach and collecting data through in-depth interviews with key informants, the study found that students' littering behavior can be categorized as active and passive. Active littering behavior is based on students' lack of concern for the environment due to insufficient knowledge of the impact of waste. Then passive littering behavior is caused by habits that delay littering even though they are aware of the waste dangers. Continuous reinforcement at school in positive and negative reinforcement through the "Green School Program" can reduce student littering behavior, both actively and passively.